Personal modus of future specialists’ self-realization - Serdiuk, Liudmyla (Social Welfare: Interdisciplinary Approach, 2014)
The paper discusses the features of personal organization and mediation of self-realization with personal characteristics at different levels of the integral indicators of self-attitude. It was found out that the implementation of personal potential is possible only at adequate self-attitude, a level of aspiration and person’s life perspective.